2010
DOI: 10.3109/17435390.2010.539713
|View full text |Cite
|
Sign up to set email alerts
|

Cationic nanoparticles induce caspase 3-, 7- and 9-mediated cytotoxicity in a human astrocytoma cell line

Abstract: On a daily basis we are exposed to cationic nanoparticulates in many different ways. They are known to distribute to many organs of the body, and while some evidence suggests that these nanoparticles are toxic to cells, the mechanism of their toxicity is not clear. Here we apply a combination of biochemical and imaging techniques to study the mechanism by which amine-modified polystyrene nanoparticles induce cell death in a human brain astrocytoma cell line. Flow cytometry analysis of cells exposed to cationic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
142
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 132 publications
(169 citation statements)
references
References 32 publications
26
142
1
Order By: Relevance
“…[4][5][6][7][8] Although several nanoparticles accumulate in cells with no acute toxicity, 3,9 some nanomaterials have been found to impact cells and this has generated nanosafety concerns. [10][11][12][13] Cytotoxic responses have been associated to nanoparticles such as metal oxide ones and fullerenes, [14][15][16][17][18] where the effect can be connected mainly to the release of toxic ions due to particle solubility, 19 oxidative stress, 17,20,21 and cationic damage. 20 Recent studies have shown that alterations of the native structure of the proteins that adsorb on the nanoparticles' surface in the context of biological fluids can trigger signaling cascades and activate inflammatory responses.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] Although several nanoparticles accumulate in cells with no acute toxicity, 3,9 some nanomaterials have been found to impact cells and this has generated nanosafety concerns. [10][11][12][13] Cytotoxic responses have been associated to nanoparticles such as metal oxide ones and fullerenes, [14][15][16][17][18] where the effect can be connected mainly to the release of toxic ions due to particle solubility, 19 oxidative stress, 17,20,21 and cationic damage. 20 Recent studies have shown that alterations of the native structure of the proteins that adsorb on the nanoparticles' surface in the context of biological fluids can trigger signaling cascades and activate inflammatory responses.…”
mentioning
confidence: 99%
“…30 This is in contrast to amine-modified PS NPs which have been shown to be toxic to in vitro CNS cell lines due to cell membrane rupture and caspase activation. 11 The 100 nm PS COOH NPs were then used for uptake, localisation and paracrine signalling studies. NP characterisation (size and zeta potential, in Supp Fig 1 and 2 respectively) indicated that in cell culture medium supplemented with 2 % bovine serum, stable dispersions were obtained and that the average size increased, while (absolute) zeta potential decreased, as a consequence of protein adsorption, protein corona formation 33 and likely partial agglomeration.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the effect of NP exposure to biological entities under the criteria of cellular transportation and long-term toxicity is therefore of paramount importance. [11][12][13][14][15][16] There has been an explosion in the number of studies of NP transport to the brain, most of which focussed on the potential of nanomaterials to cross biological barriers and/or biodistribute to the brain, and on the impacts of nanomaterials on the delicate tissues and cells of the CNS once across. [17][18][19][20][21] However, two as yet neglected areas of research are the investigation of the potential impact of NPs on the cells of the barrier themselves as a result of NP accumulation in the barrier, and the potential for signalling or other impacts to the brain without actual crossing of the NPs into the CNS (so-called indirect effects).…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, results in damage to the mitochondria and activation of caspases 3 and 7, with consequent cleavage of PARP-1, ultimately resulting in the apoptotic death of the cells [112]. Ongoing work has shown that the kinetics of the lysosome membrane damage can be correlated with the digestion of the nanoparticle protein corona in the lysosomes which allows the underlying amine groups on the nanoparticles to be re-exposed [113].…”
Section: The Signalling Concept: Interaction Of Nanoparticles With Mamentioning
confidence: 96%
“…A detailed investigation of the mechanism of toxicity induced by 50 nm amine-modified polystyrene nanoparticles following uptake by 1321N1 brain astrocytoma cells found that the nanoparticles are localized in lysosomes, whereupon the lysosomal membrane becomes destabilized, likely because of the nanoparticle's positive charge, leading to release into the cytoplasm of both nanoparticles and proteolytic enzymes such as cathepsins [112]. This, in turn, results in damage to the mitochondria and activation of caspases 3 and 7, with consequent cleavage of PARP-1, ultimately resulting in the apoptotic death of the cells [112].…”
Section: The Signalling Concept: Interaction Of Nanoparticles With Mamentioning
confidence: 99%